Preparing students for the global workplace: classroom strategies for developing english and intercultural communication skills - Simões, Anabela (2021)
According to recent OECD estimates, one-third of all jobs worldwide are likely to be transformed by technology in the next decade (World Economic Forum, 2020). This new reality calls for a reskilling effort, which to be meaningful requires individuals in general, and Higher Education Institutions in particular, to adjust and focus on the fastest-growing professions of the future. From engineering, cloud computing, data and AI to sales marketing and project management, as well as people and culture-related positions – these are some of the professional areas that will soon be most sought after. Another World Economic Forum (2018) study points at the fact that, with the inevitable rise of automation, there is a particular set of skills that is now more important than ever: the so-called social or soft skills. Therefore, when it comes to career planning, the ability to communicate and work with others, solve problems, be creative, as well as demonstrate emotional intelligence are all skills that should be perceived as the most important foundation to build upon. As the modern workplace becomes more global and interconnected, the command of foreign languages plays an ever more important role in international business relations (Brannen, Piekkari & Tietze, 2017). Simultaneously, it is also vital to know how to navigate the different identities present within culturally diverse environments (Landau, 2018; Jaidev, 2014). As language in itself is not sufficient for effective communication in such contexts, it is also important to grasp how international stakeholders think, work, and express themselves through their attitudes and behaviours (Portalla & Chen 2010; Matthews & Thakkar, 2012). From this understanding of the “other” comes empathy – which is another relevant soft skill in these challenging times. This paper aims to describe the project ‘Building Intercultural Bridges in the Classroom’ (BIBIC), whose first activity was developed within the English Language and Business Communication (ELBC) course, held at the Águeda School of Technology and Management of the University of Aveiro, during the 1st semester of academic year 2019/2020. Literature demonstrates that student-centred learning environments, where practical and more realistic assignments can be developed, are likely to be more effective and conducive to a greater level of development of both technical and interpersonal skills (Severiens, Meeuwisse & Born, 2015). With this premise in mind, the proposed activities, which were built upon the interaction of ELBC students with international volunteers from the European Solidarity Corps, seek to involve students more actively in the development of their English communication skills, as well as of their intercultural competences and other relevant technical and soft skills. In addition to the detailed description of the project, this paper also aims to present the results of a survey on students’ perception of the carried out activities. The gathered data indicates that students perceived the proposed tasks as highly rewarding and that both technical and interpersonal competences were successfully addressed.